Attitudes toward acupuncture in Hong Kong. Issue 2 (1st June 2015) - Chan, Kara; Tsang, Lennon; Fung, Timothy K.F.
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims at describing and exploring how consumers perceive acupuncture as a medical treatment in relation to biomedicine. Design/methodology/approach – Data were collected through an online survey using quota sampling. The attitudes of 879 Hong Kong residents aged 20 or above were surveyed. Questions were generated from a previous focus group study. Findings – Factor analysis found that attitude toward acupuncture consisted of five underlying dimensions, including trust in biomedicine, risks versus benefits, cure and effectiveness, qualification and skills of acupuncturists, side effects and costs and severe aftereffects. Lack of trust in acupuncturists and perceived inferiority of acupuncture to biomedicine were the major barriers of public acceptance of acupuncture. Perceived strengths of acupuncture identified were not involving taking medicine, fewer side effects and being good for preventive care. Research limitations/implications – This study used a convenience sample recruited through personal networks, so the findings cannot automatically be generalized to the rest of the population. Practical implications – There is a need to build trust in the therapy and the reputation of acupuncturists through better communication of the profession's qualification and accreditation system, as well as dissemination of clinical evidence on a long-term basis. Consumers need to be better educated about the sensations to be expected during acupuncture and the criteria for selecting an acupuncturist. Originality/value – This has been the first quantitative study focusing on Hong Kong consumers' perceptions of acupuncture.